Market power, taxation and product variety in the Brazilian automobile industry - Daniel Chaves (The University of Western Ontario, Department of Economics, 2022)
This paper empirically assesses the impact of a discontinuous tax schedule on prices, markups and product assortment in the Brazilian automobile industry. To this end, I estimate a structural, equilibrium model of demand and supply for over a hundred different models and engine sizes of automobiles. With the model estimates of price elasticities and marginal costs I quantify how market power impacts the progressivity of the discontinuous tax schedule. I also examine how firms would reposition their products to avoid the tax and quantify the impact of this repositioning on equilibrium outcomes.
Keywords: D22; D43; H23; L13; L51; L62; 330; Kraftfahrzeugsteuer; Produktdifferenzierung; Marktmacht; Kfz-Industrie; Brasilien